UTILIZING OF HPLC TECHNIQUE FOR QUALITATIVE AND QUANTITATIVE IDENTIFICATION OF SOME SECONDARY COMPOUNDS IN THE BARK AND WOOD OF Ziziphus spina-christi L. GROWING IN MOSUL - Talal Al-Takay (Mesopotamia Journal of Agriculture, 2018)
Sequence of solvents system  extraction using two different polar solvents (Benzene and Ethanol 95%) was done by using the Soxhlet apparatus then Rotary Vacuum Evaporator in order to prepare crude extract, HPLC technique was used to separate, identify and also determine some secondary compounds and its percentages from the bark and wood of Ziziphus spina-christi L.trees. The results showed a remarkable variation in the kind, number, percentage and the peak area (represented the concentration) of each separated compound. Gallic acid, Acetic acid and Salicylic acid were identified in the bark, Citric acid, Gallic acid, Acetylsalicylic acid and Salicylic acid were identified in thewood. The percentages of the compoundsat Ethanolic crude is the highest.